The raphe nuclei are the early lesion site of gastric α-synuclein propagation to the substantia nigra - Chenglu Zhang; Ruxue Bo; Tiantian Zhou; Naihong Chen; Yuhe Yuan (Elsevier, 2024)
Parkinson's disease (PD) is a neurodegeneration disease with α-synuclein accumulated in the substantia nigra pars compacta (SNpc) and most of the dopaminergic neurons are lost in SNpc while patients are diagnosed with PD. Exploring the pathology at an early stage contributes to the development of the disease-modifying strategy. Although the "gut-brain" hypothesis is proposed to explain the underlying mechanism, where the earlier lesioned site in the brain of gastric α-synuclein and how α-synuclein further spreads are not fully understood. Here we report that caudal raphe nuclei (CRN) are the early lesion site of gastric α-synuclein propagating through the spinal cord, while locus coeruleus (LC) and substantia nigra pars compacta (SNpc) were further affected over a time frame of 7 months. Pathological α-synuclein propagation via CRN leads to neuron loss and disordered neuron activity, accompanied by abnormal motor and non-motor behavior. Potential neuron circuits are observed among CRN, LC, and SNpc, which contribute to the venerability of dopaminergic neurons in SNpc. These results show that CRN is the key region for the gastric α-synuclein spread to the midbrain. Our study provides valuable details for the "gut-brain" hypothesis and proposes a valuable PD model for future research on early PD intervention.